Identification of unexpected chemical contaminants in baby food coming from plastic packaging migration by high resolution accurate mass spectrometry. (15th October 2019) - Bauer, Anna; Jesús, Florencia; Gómez Ramos, María José; Lozano, Ana; Fernández-Alba, Amadeo Rodríguez
Highlights: Development of an HRAMS method for plastic migrants from multilayer packaging. Analysis of migrating chemicals in baby food and food simulants. 39 of 42 identified potential migrants were NIAS. Quantitation and toxicity classification of main migrants. Abstract: Plastic multilayers are widely used for baby food packaging. However, it is important to consider that migration of food contact materials (FCM) into the baby food can occur. The comprehensive identification of potential migrants, including intentionally added substances (IAS) and non-intentionally added substances (NIAS), is required to assess the safety of these packaging materials. In this study, high resolution accurate mass spectrometry (HRAMS) with a data-independent acquisition method of sequential mass windows enables the detection of substances with corresponding deconvoluted fragment mass spectra. The identification of unexpected migrants present in the food simulants and in real baby food was facilitated by filtering strategies and by an in-house library. This approach has allowed the identification of 42 migrants, including eight NIAS detected for the first time. Two oligomers were quantified by means of reference standard materials at concentration levels above 0.010 mg/kg, exceeding the maximum residue levels for baby food.